Curriculum Middle Leader Practices and Teachers Perceptions of Their Effectiveness: A Study in New Zealand Secondary Schools - Camilla Highfield; Pauline Thompson; Rachel Woods (MDPI AG, 2024)
This study reports the quantitative results of middle leaders' self-reported practices and compares their responses to the perceptions of the teachers who report to them (n = 158). Likert scale questionnaires were used to measure the extent to which middle leaders focused on goal orientation, professional collaboration, effective instructional practices, and supporting teacher development within their department. The analysis provides insight into this phenomenon within six different state-funded secondary schools, with results showing middle leaders almost always rate their practices more effectively than the teachers who report to them. Common areas identified as requiring increased effectiveness were middle leaders' use of resources to support learning, use of data to support the instructional programme, and identification of effective professional learning opportunities for teachers. Reported levels of effectiveness compared with student academic achievement in the senior secondary school setting align with agreement ratings and the socio-economic status of students who attend the school. This paper highlights the need for the ongoing support of middle leaders to be provided with deliberate support and development for leading teachers.